MÉXICO Y LAS TENDENCIAS DE LA ADMINISTRACIÓN EN EL COMERCIO ELECTRÓNICO - Socorro Maday Ibarra; Patricia Grisell Leon; Hortensia Bethel Maldonado; Carla Fabiola Sotelo; Tomas J. Cuevas (European Scientific Journal, ESJ, 2013)
This essay aims to identify and describe management trends focused on e-commerce. To achieve this here is a review of sources that identify or find the development of electronic commerce in the country. Today, because of globalization, companies are facing significant changes and are forced to resort to the creation of short and long-term planning to solve current problems related to their competition. No doubt, today companies are facing a number of challenges that will allow them to be recognized and renowned.